Spectral efficient optimisation for multihop relay networks adopting HARQ schemes - Junmei Han; Yong Xi; Jibo Wei (Electronics Letters)
A joint power and rate optimisation for multihop relay networks adopting different hybrid automatic repeat request (HARQ) schemes are investigated. Specifically, Type‐I HARQ, chase‐combining‐based HARQ and schemes without HARQ are considered with practical system parameters. The optimisation problem is to adjust transmission power and rate of each node to maximise spectral efficiency under the limitations of total power consumption. However, this problem is not always mathematically tractable for three HARQ schemes. Hence, low‐complexity iterative algorithms are proposed to obtain the optimisation strategies. Numerical results demonstrate that joint optimisation strategy outperforms conventional separate optimisation strategies significantly. The impact of the path loss conditions is also investigated. It is found that performance improvement increases with increase in link unbalance.